Acrylamide and bisphenol A: two plastic additives increase platelet activation, via oxidative stress - Burgos, C. F.; Méndez, D.; Quintana, S.; Gonkowski, S.; Trostchansky, A.; Alarcón, M. (Frontiers in Pharmacology, 2025)
BackgroundSince the mid-20th century, the widespread use of plastics has led to the buildup of harmful byproducts in the environment—most notably acrylamide (AA) and bisphenol A (BPA). These chemicals are now commonly detected in human tissues, raising concerns about their potential health effects. While their presence as environmental pollutants is well known, their specific impact on platelet function and the associated cardiovascular risks remains poorly understood.MethodsTo explore how AA and BPA affect platelet physiology, we performed in vitro assays to assess platelet activation and aggregation following exposure to these compounds. We also used bioinformatic tools to identify potential protein targets in human platelets and carried out molecular docking simulations to investigate how AA and BPA interact with key enzymes involved in platelet regulation.ResultsBoth AA and BPA exposure led to a significant increase in platelet activation and aggregation, suggesting an elevated risk of thrombosis. Proteomic analysis identified around 1,230 potential protein targets, with 191 affected by AA and 429 by BPA. These proteins are primarily involved in oxidative stress, apoptosis, and signaling pathways regulated by protein kinase C (PKC), p38α-MAPK, and superoxide dismutase (SOD). Molecular modeling further revealed that AA and BPA form stable complexes with several of these enzymes, indicating direct interference with platelet function.Discussion and ConclusionOur study shows that AA and BPA can enhance platelet reactivity and aggregation, which are key factors in the development of cardiovascular disease (CVD). By identifying specific molecular pathways and targets affected by these pollutants, we provide new insights into their potential role in promoting thrombotic conditions. These findings highlight the urgent need for greater public health awareness and stronger regulatory efforts to reduce human exposure to AA and BPA.